Indonesia Hadapi Transisi “Oleng”: Perubahan Adalah Jawaban - Rizal Ramli (Budapest International Research and Critics University, 2016)
Changes always happen in this earth. Hence, this article wants to show how the nation needs a change. SBY-Boediono government is very weak and merely does not have firm sociological roots. Today government is like “Sand House” which is bound by image glue. Now, that image glue gradually melts after having given “deceit stamp” by some prominent religious figures, intelectuals, movement figures, workers, youths and students, and scandals involving the ruling party. Therefore, the fate of the Image Order will soon come to an end. The sand house will collapse, and it will not leave crucial problems, let alone ideological matters.